Numerical and experimental studies of rotorcraft icing phenomena - Kim, J.; Sankar, L.; Palacios, J.; Kreeger, R.E. (My University, 2015)
With support from and collaboration with NASA and the DoD's Vertical Lift Research Center of Excellence, research teams at Georgia Institute of Technology and The Pennsylvania State University are conducting computational and experimental studies on ice accretion for representative 2-D and 3-D configurations. A wealth of data including ice shapes, surface pressure data, and 3-D performance data (such as sectional lift, drag, thrust, torque) are being acquired. Details of the ice modelling tools are presented along with selected validation studies. Advantages and shortcomings of the methods are discussed as are our teams' prospects for the future.
Keywords: Operational Aspects